Stem Cell Therapy and Exercise for Treatment of Intervertebral Disc Degeneration - Bo Li; Yunmei Yang; Lan Wang; Guanghua Liu (Stem Cells International)
As part of the motor system, intervertebral disc (IVD) is a complicated tissue with multiple components. The degeneration of IVD may result in low back pain (LBP), which strongly impairs quality of life. Various causes are related to the degeneration of IVD, including cell senescence, hydration lost, and inflammation. Stem cells founded in different tissues have attracted the interest of the researchers and clinicians to study the implication of these cells in the treatment for tissue injury and degeneration. In this report, we will review the study of stem cells in the treatment for IVD degeneration. On the other hand, the effect of exercise on IVD degeneration and the relationship between IVD degeneration and musculoskeletal disorders like sarcopenia are discussed.